A randomized controlled trial investigating the effect of Pycnogenol and Bacopa CDRI08 herbal medicines on cognitive, cardiovascular, and biochemical functioning in cognitively healthy elderly people: the Australian Research Council Longevity Intervention (ARCLI) study protocol (ANZCTR12611000487910) - Stough Con K; Pase Matthew P; Cropley Vanessa; Myers Stephen; Nolidin Karen; King Rebecca; Camfield David; Wesnes Keith; Pipingas Andrew; Croft Kevin; Chang Dennis; Scholey Andrew B (Nutrition Journal, 2012)
Abstract Background One of the major challenges associated with our ageing population is the increasing incidence of age-associated cognitive decline, which has significant implications for an individual's ability to lead a productive and fulfilling life. In pure economic terms the costs of ageing reflects decreased productivity and engagement with the workforce. The maintenance of brain health underpinning intact cognition is a key factor to maintaining a positive, engaged, and productive lifestyle. In light of this, the role of diet, including supplementation with nutritional and even pharmacological interventions capable of ameliorating the neurocognitive changes that occur with age constitute vital areas of research. Methods In order to reduce cognitive ageing, the ARC longevity intervention (ARCLI) was developed to examine the effects of two promising natural pharmacologically active supplements on cognitive performance. ARCLI is a randomized, placebo-controlled, double-blind, 3-arm clinical trial in which 465 participants will be randomized to receive an extract of Bacopa monnieri (CDRI08 300 mg/day), Pycnogenol (150 mg/day), or placebo daily for 12 months. Participants will be tested at baseline and then at 3, 6 and 12 months post-randomization on a wide battery of cognitive, neuropsychological and mood measures, cardiovascular (brachial and aortic systolic and diastolic blood pressures as well as arterial stiffness), biochemical (assays to measure inflammation, oxidative stress and safety) as well as genetic assessments (telomere length and several Single Nucleotide Polymorphisms). The primary aim is to investigate the effects of these supplements on cognitive performance. The secondary aims are to explore the time-course of cognitive enhancement as well as potential cardiovascular and biochemical mechanisms underpinning cognitive enhancement over the 12 months of administration. ARCLI will represent one of the largest and most comprehensive experimental clinical trials in which supplements are administered to elderly participants. Results from ARCLI may help develop novel preventative health practices and nutritional/pharmacological targets in the elderly for cognitive and brain health. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12611000487910